Choroidal Microvascular Dropout in Primary Open-angle Glaucoma Eyes With Disc Hemorrhage. Issue 3 (March 2019) - Rao, Harsha L.; Sreenivasaiah, Shruthi; Dixit, Shivani; Riyazuddin, Mohammed; Dasari, Srilakshmi; Venugopal, Jayasree P.; Pradhan, Zia S.; Puttaiah, Narendra K.; Devi, Sathi; Mansouri, Kaweh; Webers, Carroll A.B.; Weinreb, Robert N.
Abstract : Purpose: The main purpose of this study was to compare the prevalence of choroidal microvascular dropout (CMvD) in primary open-angle glaucoma (POAG) eyes with and without disc hemorrhage (DH). Methods: In a cross-sectional study, 44 eyes of 44 control subjects, 32 eyes of 32 POAG patients with DH, and 41 eyes of 41 POAG patients without DH underwent visual fields (VFs), optical coherence tomography (OCT) and OCT angiography (OCTA). Presence of CMvD was evaluated on the choroidal OCTA slab. VF defect in the glaucoma eyes were classified into initial nasal defect, initial parafoveal scotoma, and combined nasal and parafoveal defect. Results: CMvD was detected in 17 POAG eyes with DH (53.1%) and 13 POAG eyes without DH (31.7%; P =0.06). On univariate analysis, CMvD in POAG eyes was associated with DH [odds ratio (OR): 2.44, P =0.06] and measures of glaucoma severity: VF mean deviation (OR: 0.85, P =0.02), retinal nerve fiber layer thickness (OR: 0.95, P =0.03), and peripapillary vessel density (OR: 0.94, P =0.09). On multivariate models that accounted for the measures of glaucoma severity, CMvD in POAG eyes was statistically significantly associated with DH (OR≥3, P <0.05). CMvD was more frequently seen in eyes with initial parafoveal scotoma than initial nasal defect both in POAG eyes with DH ( P =0.06) and POAG eyes without DH ( P <0.001). Conclusions: Prevalence of CMvD was significantly greater in POAG eyes with DH compared with POAG eyes without DH. CMvD in POAG eyes was also significantly associated with central VF defects and greater severity of glaucomatous damage.